Synthesis, reactions, and applications of pyrimidine derivatives - Mahmoud S. Tolba (Growing Science, 2022)
Pyrimidine compounds continue to attract great interest in the field of organic synthesis due to their various chemical and biological applications observed, especially in recent times. As a result, this review covering some periods from 1957 to 2021 has been prepared to discuss some of the structural pathways of these compounds as well as some of their interactions and applications.